1981
DOI: 10.1128/aem.41.3.737-745.1981
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of thirteen intestinal microorganisms capable of 7 alpha-dehydroxylating bile acids

Abstract: Thirteen anaerobic bacteria capable of performing the 7a-dehydroxylation of both cholic acid and chenodeoxycholic acid were isolated from human feces and also from sewage. Ten organisms from heat-treated samples were species of Clostridium identical or closely related to the Clostridium bifermentans-C. sordellii group and consisted of four strains elaborating 7a-dehydroxylase alone and six strains capable of catalyzing both 7a-dehydrogenation and 7a-dehydroxylation. The remaining three organisms, recovered fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 27 publications
1
64
1
Order By: Relevance
“…The samples were homogenized in 100 mM HEPES buffer (pH 7.5) and appropriate dilutions of the fecal suspensions were plated on a nutritionally poor agar medium, 1/4 × Gifu anaerobic medium (GAM) (1/4GAM) (Nissui Pharmaceutical Co. Ltd, Tokyo, Japan), containing 15 g L −1 agar to avoid overlapping of bacterial colonies by limiting the growth of rapidly growing bacterial species, thereby facilitating the isolation of slow growers. After 2–7 days of culture, the colonies on the plates were picked and cultured either in 200 μL of GAM, liquid casein yeast (LCY), or peptone–yeast extract (PY) broth containing 0.1 mM CA or CDCA in 96‐well microtiter plates for 48 h. The compositions of LCY and PY broth were described by Lepercq et al (2004) and in Hirano et al (1981), respectively. The bile acid conversion activity of each isolate was detected by thin‐layer chromatography (TLC) as described below; all positive cultures that gave disappearance of substrate spot and/or appearance of new spot(s) corresponding to possible reaction products were tested for reproducibility.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were homogenized in 100 mM HEPES buffer (pH 7.5) and appropriate dilutions of the fecal suspensions were plated on a nutritionally poor agar medium, 1/4 × Gifu anaerobic medium (GAM) (1/4GAM) (Nissui Pharmaceutical Co. Ltd, Tokyo, Japan), containing 15 g L −1 agar to avoid overlapping of bacterial colonies by limiting the growth of rapidly growing bacterial species, thereby facilitating the isolation of slow growers. After 2–7 days of culture, the colonies on the plates were picked and cultured either in 200 μL of GAM, liquid casein yeast (LCY), or peptone–yeast extract (PY) broth containing 0.1 mM CA or CDCA in 96‐well microtiter plates for 48 h. The compositions of LCY and PY broth were described by Lepercq et al (2004) and in Hirano et al (1981), respectively. The bile acid conversion activity of each isolate was detected by thin‐layer chromatography (TLC) as described below; all positive cultures that gave disappearance of substrate spot and/or appearance of new spot(s) corresponding to possible reaction products were tested for reproducibility.…”
Section: Methodsmentioning
confidence: 99%
“…Which bacteria in human intestinal microflora correspond to the present clostridia in rats is not yet known but some species of human intestinal bacteria have been reported to have 7α-dehydroxylation activity (4)(5)(6)(7)(8)(9)(10)(11), although the counts of 7α-dehydroxylating positive bacteria were as low as 10 5 -10 6 counts per g wet weight feces. Stellwag and Hylemon (7) reported that the 7α-dehydroxylation activity of mixed fecal bacteria was 0.06-0.012 µmol/h·mg protein for cholic acid in an in vitro system.…”
Section: Discussionmentioning
confidence: 99%
“…Deconjugation activity is found in many species of intestinal bacteria (3) but those possessing 7α-dehydroxylation activity are limited. 7α-Dehydroxylating activity is found in Clostridium (4-7), Bacteroides (8), Lactobacillus (9), Eubacterium (4,5,10,11) and in as yet unclassified intestinal bacteria (4,5). The population of these 7α-dehydroxylating bacteria is not large, and their counts are only 10 5 -10 6 per g wet feces, while the counts of dominant intestinal bacteria possessing no 7α-dehydroxylation activity (12) are around 10 11 -10 12 per g wet feces.…”
mentioning
confidence: 99%
“…casei 1001 were obtained from the Yakult Central Institute (Tokyo). Strain HD-17 is an unusually coiled anaerobic, gram-positive, nonsporeforming rod isolated from human feces (2). The five strains of Peptostreptococcus productus, the two strains of Eubacterium lentum and the five strains of an E. lentum-like organism were isolated from human feces.…”
Section: Methodsmentioning
confidence: 99%